This is the complete guide to all Trigonometric identities, memorize here, remember everything forever.
Fundamental Pythagorean Identity
sin²(x) + cos²(x) = 1
Pythagorean Identity with tan and sec
1 + tan²(x) = sec²(x)
Pythagorean Identity with cot and csc
1 + cot²(x) = csc²(x)
sin(θ) in terms of its reciprocal
sin(θ) = 1/csc(θ)
cos(θ) in terms of its reciprocal
cos(θ) = 1/sec(θ)
tan(θ) in terms of its reciprocal
tan(θ) = 1/cot(θ)
csc(θ) in terms of its reciprocal
csc(θ) = 1/sin(θ)
sec(θ) in terms of its reciprocal
sec(θ) = 1/cos(θ)
cot(θ) in terms of its reciprocal
cot(θ) = 1/tan(θ)
Is sin(x) even or odd?
sin(-x) = -sin(x) (odd)
Is cos(x) even or odd?
cos(-x) = cos(x) (even)
Is tan(x) even or odd?
tan(-x) = -tan(x) (odd)
Is csc(x) even or odd?
csc(-x) = -csc(x) (odd)
Is sec(x) even or odd?
sec(-x) = sec(x) (even)
Is cot(x) even or odd?
cot(-x) = -cot(x) (odd)
sin(π/2 - x)
sin(π/2 - x) = cos(x)
cos(π/2 - x)
cos(π/2 - x) = sin(x)
tan(π/2 - x)
tan(π/2 - x) = cot(x)
cot(π/2 - x)
cot(π/2 - x) = tan(x)
sec(π/2 - x)
sec(π/2 - x) = csc(x)
csc(π/2 - x)
csc(π/2 - x) = sec(x)
sin(a + b)
sin(a + b) = sin(a)cos(b) + cos(a)sin(b)
sin(a - b)
sin(a - b) = sin(a)cos(b) - cos(a)sin(b)
cos(a + b)
cos(a + b) = cos(a)cos(b) - sin(a)sin(b)
cos(a - b)
cos(a - b) = cos(a)cos(b) + sin(a)sin(b)
tan(a + b)
tan(a + b) = (tan(a) + tan(b)) / (1 - tan(a)tan(b))
tan(a - b)
tan(a - b) = (tan(a) - tan(b)) / (1 + tan(a)tan(b))
sin(2x)
sin(2x) = 2sin(x)cos(x)
cos(2x) (primary form)
cos(2x) = cos²(x) - sin²(x)
Alternative form for cos(2x)
cos(2x) = 2cos²(x) - 1 = 1 - 2sin²(x)
tan(2x)
tan(2x) = (2tan(x)) / (1 - tan²(x))
sin(3x)
sin(3x) = 3sin(x) - 4sin³(x)
cos(3x)
cos(3x) = 4cos³(x) - 3cos(x)
tan(3x)
tan(3x) = (3tan(x) - tan³(x)) / (1 - 3tan²(x))
sin(x/2) in terms of cos(x)
sin(x/2) = ±√((1 - cos(x)) / 2)
cos(x/2) in terms of cos(x)
cos(x/2) = ±√((1 + cos(x)) / 2)
tan(x/2) (common form)
tan(x/2) = sin(x) / (1 + cos(x)) or (1 - cos(x)) / sin(x)
Product-to-Sum: sin(A)sin(B)
sin(A)sin(B) = 1/2[cos(A - B) - cos(A + B)]
Product-to-Sum: cos(A)cos(B)
cos(A)cos(B) = 1/2[cos(A - B) + cos(A + B)]
Product-to-Sum: sin(A)cos(B)
sin(A)cos(B) = 1/2[sin(A + B) + sin(A - B)]
Sum-to-Product: sin(A) + sin(B)
sin(A) + sin(B) = 2sin((A + B)/2)cos((A - B)/2)
Sum-to-Product: sin(A) - sin(B)
sin(A) - sin(B) = 2cos((A + B)/2)sin((A - B)/2)
Sum-to-Product: cos(A) + cos(B)
cos(A) + cos(B) = 2cos((A + B)/2)cos((A - B)/2)
Sum-to-Product: cos(A) - cos(B)
cos(A) - cos(B) = -2sin((A + B)/2)sin((A - B)/2)
Power-Reducing: sin²(x)
sin²(x) = (1 - cos(2x))/2
Power-Reducing: cos²(x)
cos²(x) = (1 + cos(2x))/2
Power-Reducing: tan²(x)
tan²(x) = (1 - cos(2x))/(1 + cos(2x))
De Moivre’s Theorem
(cosθ + isinθ)ⁿ = cos(nθ) + isin(nθ)
Euler’s Formula
e^(iθ) = cos(θ) + isin(θ)
Combine asin(x) + bcos(x)
asin(x) + bcos(x) = Rsin(x + φ) where R = √(a² + b²), tan(φ) = b/a.
arcsin(x ± y)
arcsin(x ± y) = arcsin(x) ± arcsin(y) (Valid where x ± y is within the range of arcsin function)
arccos(x ± y)
arccos(x ± y) = arccos(x) ± arccos(y) (Valid where x ± y is within the range of arccos function)
Periodic Identity of sin(x)
sin(x) has a period of 2π, meaning sin(x + 2π) = sin(x) for all x.
Periodic Identity of cos(x)
cos(x) has a period of 2π, meaning cos(x + 2π) = cos(x) for all x.
Periodic Identity of csc(x)
csc(x) has a period of 2π, meaning csc(x + 2π) = csc(x) for all x.
Periodic Identity of sec(x)
sec(x) has a period of 2π, meaning sec(x + 2π) = sec(x) for all x.
Periodic Identity of tan(x)
tan(x) has a period of π, meaning tan(x + π) = tan(x) for all x.
Periodic Identity of cot(x)
cot(x) has a period of π, meaning cot(x + π) = cot(x) for all x.
Law of Sines
a/sin(A) = b/sin(B) = c/sin(C) for triangle with sides a, b, c opposite angles A, B, C respectively.
Law of Cosines (version 1)
c² = a² + b² - 2ab * cos(C)
Law of Cosines (version 2)
a² = b² + c² - 2bc * cos(A)
Law of Cosines (version 3)
b² = a² + c² - 2ac * cos(B)
Law of Tangents (version 1)
(a - b) / (a + b) = tan((A - B) / 2) / tan((A + B) / 2)
Law of Tangents (version 2)
(b - c) / (b + c) = tan((B - C) / 2) / tan((B + C) / 2)
Law of Tangents (version 3)
(c - a) / (c + a) = tan((C - A) / 2) / tan((C + A) / 2)
Cofunction Identity for Sin and Cos
sin(π/2 - x) = cos(x)
Cofunction Identity for Cos and Sin
cos(π/2 - x) = sin(x)
Cofunction Identity for Tan and Cot
tan(π/2 - x) = cot(x)
Cofunction Identity for Cot and Tan
cot(π/2 - x) = tan(x)
Cofunction Identity for Sec and Csc
sec(π/2 - x) = csc(x)
Cofunction Identity for Csc and Sec
csc(π/2 - x) = sec(x)
Mollweide's Formula
For a triangle with angles A, B, and C, and opposite sides a, b, and c, Mollweide's formula states: asin(A) + bsin(B) = c*sin(C).
Double Angle Identity for Sine
sin(2x) = 2sin(x)cos(x)
Double Angle Identity for Cosine
cos(2x) = cos²(x) - sin²(x) = 2cos²(x) - 1 = 1 - 2sin²(x)
Half Angle Identity for Sine
sin(x/2) = ±√((1 - cos(x)) / 2)
Half Angle Identity for Cosine
cos(x/2) = ±√((1 + cos(x)) / 2)
Half Angle Identity for Tangent
tan(x/2) = sin(x) / (1 + cos(x)) = (1 - cos(x)) / sin(x)